Modelling of permeability characteristics of soil-fly ash-bentonite cut-off wall using response surface method - Dungca, Jonathan R. (Animo Repository, 2016)
In order to prevent the contamination the groundwater, by restricting the horizontal movement of leachate, cut-off walls were recommended [1]. Currently, one of the factors in designing cut-off walls is to provide efficient and relatively inexpensive means of containing contaminants. In order to obtain acceptable permeability, it was suggested by Baxter [2] to provide a mix of 96% soil and 4% bentonite in the design of cut-off walls, but bentonite is relatively expensive, thus the viability of fly ash as a replacement for bentonite was considered. Soil mixtures were proposed and rigorous laboratory tests were performed to determine the individual properties of the said soil mixtures. Tests for specific gravity, soil index property, relative density, microscopic characterizations, elemental composition and permeability were performed to garner data that were utilized for the Response Surface Method Permeability models. The minimum permeability requirements for the cut-off wall were achieved using various mixtures of soil-bentonite-fly ash. © 2015, Int. J. of GEOMATE. All rights reserved.